Introduction to administrative law - Hawke, Neil. (New Delhi, 1989)
This book endeavors to introduce the discipline of international law in such a way as to clarify and order a dauntingly complex and variegated subject. Three questions more or less structure the text: What are international legal rules? What is international legal process? What role does international law play in international relations? Answering the questions in order yields an unremarkable organization for an international law book except that the law of treaties is discussed alongside the topic of treaties as a source of international law, public international arbitration and the International Court follow immediately after the role of international law in the municipal courts, and as aforementioned, the "private" as well as the "public" part of international law is introduced.
Keywords: Administrative law